2015
DOI: 10.1080/13803395.2015.1091065
|View full text |Cite
|
Sign up to set email alerts
|

Increased attentional load moves the left to the right

Abstract: Introduction Unilateral brain damage can heterogeneously alter spatial processing. Very often brain-lesioned patients fail to report (neglect) items appearing within the contralesional space. Much less often patients mislocalize items' spatial position. We investigated whether a top-down attentional load manipulation (dual-tasking), known to result in contralesional omissions even in apparently unimpaired cases, might also induce spatial mislocalizations. Method Nine right-hemisphere damaged patients performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Patients with neglect mislabeled items belonging to the past as being “future” items both in recall and in recognitions tasks significantly more than participants without neglect did. This spatial distortion closely mirrors spatial mislocalizations in the visual space whereby contralesional targets, under demanding tasks, are reported to appear in the ipsilesional space [ 27 ].…”
Section: Introductionmentioning
confidence: 67%
“…Patients with neglect mislabeled items belonging to the past as being “future” items both in recall and in recognitions tasks significantly more than participants without neglect did. This spatial distortion closely mirrors spatial mislocalizations in the visual space whereby contralesional targets, under demanding tasks, are reported to appear in the ipsilesional space [ 27 ].…”
Section: Introductionmentioning
confidence: 67%
“…In the dual-task context, he made 0% omissions but, on 8% of the trials, he reported having seen a stimulus in both parts of the screen, while there was a stimulus in the upper part only. This phenomenon is reminiscent of synchiria (Bonato & Cutini, 2016).…”
Section: Casementioning
confidence: 97%
“…This idea is also consistent with other (above-mentioned) phenomena related to attentional deficits that may follow parietal damage: when content features are not tightly bound to the representation of their locations, because of a damage to the attentional mechanisms subtending this binding process, false conjunctions of features of different objects (e.g., in Balint patients) or allochiric misallocation of objects toward the focus of attention (e.g., in UN patients) can occur. Accordingly, an increased number of allochiric misallocations in UN patients has been observed when the availability of patients' attentional resources were further reduced by increasing the attentional load, that is, under dual-task (vs. single-task) conditions (Bonato and Cutini, 2016).…”
mentioning
confidence: 99%